Classical Guidance as an Effective Solution to Overcome Bullying Behavior at SMPN 1 Juntinyuat - Akhnaf Adilatul Fakhiroh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Bullying in schools is a serious problem that negatively impacts students' mental and physical health and academic achievement. This research was motivated by the high incidence of bullying and the lack of understanding of this issue among students at SMPN 1 Juntinyuat. To address these challenges, the Community Service Program team implemented an Anti-Bullying Classical Guidance program as a preventive and rehabilitative measure. The program's primary objective was to raise students' awareness of the definition, forms, and negative impacts of bullying, as well as to provide them with skills to prevent and address it. The implementation method used was interactive classical guidance, a combination of lectures, group discussions, and Q&A sessions centered on 9th-grade students (approximately 290 participants). The program's effectiveness was measured quantitatively by comparing pre-test and post-test scores using Normalized Gain (N-Gain) analysis. The results showed a significant increase in understanding, with an average N-Gain score of 0.95, categorized as High. This achievement confirms that classical guidance is effective in transferring anti-bullying knowledge and provides a strong foundation for creating a safe and supportive school environment.